Are online searches for the novel coronavirus (COVID-19) related to media or epidemiology? A cross-sectional study - Szmuda, Tomasz (Int J Infect Dis, 2020)
BACKGROUND: Previous studies on the novel Coronavirus (COVID-19) have found strong correlations between online searches and the epidemiology of the disease. AIM: Our aim was to determine if online searches for COVID-19 related to international media announcements or national epidemiology. METHODS: Searches for “coronavirus” were made on Google Trends from December 31, 2019 to April 13, 2020 for 40 European countries. The online COVID-19 searches for all countries were correlated with each other. COVID-10 epidemiology (i.e. incidence and mortality) was correlated with the national online searches. Major announcements by the World Health Organization (WHO) were taken into consideration with peaks in online searches. Correlations were made using Spearman's rank correlation coefficient. RESULTS: Overall, the online searches for COVID-19 were not correlated with the actual incidence and mortality of COVID-19. The mean Spearman correlation for incidence was 0.20 (range −0.66 to 0.76) and for mortality was 0.35 (range −0.75 to 0.85). Online searches in Europe were all strongly synchronized with each other; a mean Spearman correlation of 0.93 (range 0.62 to 0.99). CONCLUSIONS: Online searches for COVID-19 in Europe are not correlated with epidemiology but strongly correlated with international WHO announcements. Our study challenges previous Google Trends studies and emphasizes the role of the WHO in raising awareness of a new disease.